Quinine monotherapy for treating uncomplicated malaria in the era of artemisinin-based combination therapy: an appropriate public health policy? - Yeka, Adoke; Achan, Jane; D’Alessandro, Umberto; Talisuna, Ambrose O. (The Lancet infectious diseases, 2009)
Several African countries that have adopted artemisinin-based combination therapy (ACT) as fi rst-line treatment of uncomplicated Plasmodium falciparum malaria also use quinine monotherapy as second-line therapy. This policy goes against WHO recommendations for combination therapy and could be considered an inappropriate public health policy. Adherence to a 7-day quinine treatment schedule is likely to be poor and may increase the risk of selecting resistant parasites. Furthermore, because quinine has limited post-treatment prophylaxis, it will not prevent, in areas of intense transmission, recurrent malaria infections, which can lead to additional morbidity, including anaemia. Therefore, ACTs and not quinine should be used as second-line treatment, because these are well tolerated, highly effi cacious, and have the advantage of reducing gametocyte carriage and consequently malaria transmissibility, particularly in areas of less intense transmission.
Keywords: Quinine monotherapy; Malaria; Treating